Criminal Environmental Policy: the Moscow Authorities Practice - Dubovik, Olga L. (Sociologija. Mintis ir veiksmas, 2007)
Criminal laws in most countries in most periods envisaged liability for crimes contemporary considered as environmental (poaching, water pollution, etc.). However, before the eighties of the last century, such crimes have never been legislatively consolidated and were generally incorporated in different sections of formal acts, until international community and legislative authorities, as well as scientist have launched certain measures to improve that situation – a common European approach to environmental crime combating activities and implementation of this approach through legislative acts. So the article examines the evolution of criminal environmental legislation system, referring to scientific research and international initiatives undertaken in this concern. It also discusses criminal environmental policy concept and structure, presenting its main components. At the same time the author emphasizes that the formation of criminal environmental policy in general is still in progress and discusses factors which prevent this policy from being stable, formalized and integrated. The author also stresses that reforms in the legislation and establishment of new authorizes bodies undertaken by international community and by certain countries individually did not achieve the main goals, since the number of committed crimes is still increasing and the consequences of such crimes are becoming more severe. These and other circumstances require special research of environmental crime in order to discover new trends of this type of crime and to find new measures to combat it. So the article continues to discuss this problem referring to data presenting current situation with environmental crime in Russia.
Keywords: environmental crime; legislation; domestic policy